Stinging or Venomous Insects and Related Pests - P.G. Koehler; D.E. Short (EDIS)
This document provides an overview of stinging or venomous insects and related pests in Florida. It categorizes venoms into four types: vesicating, neurotoxic, cytolytic/hemolytic, and hemorrhagic. The article emphasizes the importance of allergic reactions, which are often more severe than the toxic effects. It outlines immediate actions to take following stings or bites and offers prevention tips. Additionally, it describes common venomous arthropods, including bees, wasps, scorpions, spiders, fire ants, velvet ants, wheel bugs, blister beetles, and stinging caterpillars, along with control measures for each. Publication date: October 1994.